Memórias da política, políticas da memória: o centenário da Confederação do Equador no Ceará (1924) - Valente, Paulo Giovanni Gomes (2014)
Commemorative actions call individuals of a certain group or society to recollect certain past facts collectively. It is regarded as even more ambitious when the celebrations intend to create or reinforce identity bonds inside of a political community. The participation of Ceará in The Confederation of the Equator was suitable as source of creation to that moment. Memories of that political event occurred in 1824 and it has been resumed in the first years of Proclamation of Republic of Brazil, by means of some political actions of memory, several readings and interpretations had been formulated from that event. The year of 1924 is marked by the turn of the century. A century later what possibly remains as vestige of political fights in those first moments of Brazil’s post-independence? Which characters have been part of The Confederation of the Equator in Ceará and have been recognized as cearense heroes? Which gaps had been used deliberately to eternize those event memories? And what about historical production, what is its role in this process? Researching on books, newspapers, magazines, almanacs, and public places intend to elaborate some considerations concerning to this relation between politics and prior memories.